Systematic review and meta-analysis: bezafibrate in patients with primary biliary cirrhosis - Yin, Qin (Drug Des Devel Ther, 2015)
BACKGROUND AND AIM: Ursodeoxycholic acid (UDCA) is the standard treatment for primary biliary cirrhosis (PBC), but not all cases respond well. Evidence has shown that combination therapy of UDCA with bezafibrate significantly improved liver function. A meta-analysis was performed to assess the efficacy and safety of UDCA and bezafibrate combination therapy in the treatment of PBC. RESULTS: Nine trials, with a total of 269 patients, were included in the analysis. The bias risk of these trials was high. Compared with UDCA alone, the combination with bezafibrate improved the Mayo risk score (mean difference [MD], 0.60; 95% confidence interval [CI], 0.25–0.95; P=0.0008) and liver biochemistry: alkaline phosphatase (MD, −238.21 IU/L; 95% CI, −280.83 to −195.60; P<0.00001); gamma-glutamyltransferase (MD, −38.23 IU/L; 95% CI, −50.16 to −25.85; P<0.00001); immunoglobulin M (MD, −128.63 IU/L; 95% CI, −151.55 to −105.71; P<0.00001); bilirubin (MD, −0.20 mg/dL; 95% CI, −0.33 to −0.07; P=0.002); triglycerides (MD, −26.84 mg/dL; 95% CI, −36.51 to −17.17; P<0.0001); total cholesterol (MD, −21.58 mg/dL; 95% CI, −30.81 to −12.34; P<0.0001), and serum alanine aminotransferase (MD, −10.24 IU/L; 95% CI, −12.65 to −78.5; P<0.00001). However, combination therapy showed no significant differences in the incidence of all-cause mortality or pruritus, and may have resulted in more adverse events (risk ratio [RR], 0.22; 95% CI, 0.07–0.67; P=0.008). CONCLUSION: Combination therapy improved liver biochemistry and the prognosis of PBC, but did not improve clinical symptoms or incidence of death. Attention should be paid to adverse events when using bezafibrate.